DESIGN OF AWSTRAL (AUTOMATIC WARNING SYSTEM AT TRAFFIC LIGHT) IN PALOPO CITY USING PROTOTYPE METHOD - Nirsal, Nirsal; Saputra, Ardiansyah (Informatika, Universitas Jenderal Soedirman, 2024)
The growth of the population, which affects traffic congestion issues, has shown that effective traffic management is crucial, especially at intersections with high vehicle volumes. Currently, traffic control methods using hand signals from traffic officers are considered less effective, with controllers often experiencing disruptions with traffic lights. To address this issue, it is necessary to design a prototype of an Automatic Warning System at Traffic Lights (AWSTRAL). This system will be designed to provide automatic warnings to drivers when there is a disruption in the traffic light or an unsafe traffic situation. This research uses a prototyping approach to design AWSTRAL, which consists of several main components, including traffic sensors, data processing systems, and warning displays. The result of this research is a prototype that, when a disruption in the traffic light or an unsafe traffic situation is detected, AWSTRAL will automatically activate warning displays located around the intersection. The warning displays will inform drivers of unsafe conditions and provide instructions on actions to be taken, such as stopping or proceeding with caution. The use of AWSTRAL will help reduce the risk of traffic accidents and improve road safety. Additionally, by providing automatic warnings, AWSTRAL will help optimize traffic flow and reduce congestion at intersections.